Evaluating the digital divide: the Silver Surfer's perspective. (13th January 2010) - Choudrie, Jyoti; Grey, Susan; Tsitsianis, Nicholas
The aim of this paper is to explore and ascertain using an information systems perspective evaluation framework, the factors that encouraging the adoption and usage of online products and services; namely, in this case, broadband, within one particular population group – the Silver Surfer. Data were collected using email, interviews and an online survey. The findings of this study illustrate that technical factors are not of primary importance. Non-technical factors were considered to be fundamental and clearly need to be taken into consideration when encouraging Silver Surfers to become online interactive. What was also discovered is that interest, whether in technological or non-technological factors, as well as communication are very pertinent in adopting and using technology. This research should offer a substantial contribution to various stakeholders including government agencies, management consulting firms, Internet Service Providers and IT organisations wanting to identify the online interactions of Silver Surfers.